Inactivating effects of the lactoperoxidase system on bacterial lyases involved in oral malodour production. Issue 10 (October 2015) - Nakano, Manabu; Shin, Kouichirou; Wakabayashi, Hiroyuki; Yamauchi, Koji; Abe, Fumiaki; Hironaka, Shouji
Abstract : N/A: The main components of oral malodour have been identified as volatile sulfur compounds (VSCs), including hydrogen sulfide (H2 S) and methyl mercaptan (CH3 SH). The lactoperoxidase (LPO) system (consisting of LPO, glucose oxidase, glucose and thiocyanate) was previously shown to exhibit antimicrobial activities against some oral bacteria in vitro and suppressive effects on VSCs in mouth air in a clinical trial. Here, we examined the in vitro effects of the LPO system on the activities of the bacterial lyases involved in the production of VSCs by oral anaerobes. The exposure of crude bacterial extracts of Fusobacterium nucleatum and Porphyromonas gingivalis or purified methionine γ‐lyase to the LPO system resulted in the inactivation of their lyase activities through l‐cysteine and l‐methionine, which was linked to the production of H2 S and CH3 SH, respectively. The exposure of living F. nucleatum and P. gingivalis cells to the LPO system resulted in the suppression of cell numbers and lyase activities. The inactivation of the crude bacterial extracts of F. nucleatum and purified methionine γ‐lyase by the LPO system was partly recovered by the addition of DTT. Therefore, the LPO system may inactivate bacterial lyases including methionine γ‐lyase by reacting with the free cysteine residues of lyases. These results suggested that the LPO system suppresses the production of VSCs not only through its antimicrobial effects, but also by its inactivating effects on the bacterial lyases of F. nucleatum and P. gingivalis .